1983
DOI: 10.1901/jaba.1983.16-283
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Side Effects of Reward

Abstract: The negative side effects of aversive control have been extensively discussed in clinical literature and textbooks. The symmetry between aversive and appetitive control in basic experimental research implies that parallel negative side effects of reward exist. These negative side effects are described and their implications for clinical practice and research are discussed.DESCRIPTORS: reinforcement, punishment, iatrogenic illness, symptom substitution, generalization A behavioral psychologist, Dr. B, once had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0
7

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 39 publications
5
54
0
7
Order By: Relevance
“…More accurate discrimination occurred with the houselight than with brief food rewards, and the primary basis of this difference was that the food rewards induced a higher rate of perseverative responding (e.g., responding to the middle key on the second position ofthe above sequence). Luck et al noted that the superiority of conditioned reinforcement contingencies in similar conditional discrimination problems had been reported by several previous investigators, and that the perseverative effects of primary reinforcement should be considered to be another example of the negative side effects of reward that have been highlighted by Balsam and Bondy (1983). By reducing the interfering effects of such perseveration, conditioned reinforcement contingencies apparently allowed the conditional relations between current behavior and previous behavior to be discriminated more readily.…”
Section: Practical Uses Of Conditioned Reinforcementmentioning
confidence: 73%
“…More accurate discrimination occurred with the houselight than with brief food rewards, and the primary basis of this difference was that the food rewards induced a higher rate of perseverative responding (e.g., responding to the middle key on the second position ofthe above sequence). Luck et al noted that the superiority of conditioned reinforcement contingencies in similar conditional discrimination problems had been reported by several previous investigators, and that the perseverative effects of primary reinforcement should be considered to be another example of the negative side effects of reward that have been highlighted by Balsam and Bondy (1983). By reducing the interfering effects of such perseveration, conditioned reinforcement contingencies apparently allowed the conditional relations between current behavior and previous behavior to be discriminated more readily.…”
Section: Practical Uses Of Conditioned Reinforcementmentioning
confidence: 73%
“…In Cameron, Banko, and Pierce's study, negative effects were shown in high-interest tasks when the rewards were tangible, expected (offered beforehand), and loosely tied to the level of performance (Cameron et al, 2001). Balsam and Bondy (1983) also argued the symmetry between aversive and appetitive control in basic experimental research implied that parallel negative side effects of reward did exist. Therefore, the effectiveness of reward and punishment still remains unclear.…”
mentioning
confidence: 99%
“…The positive evaluation for painting was intended to establish an expectancy of evaluation during subsequent collage construction. As predicted, the children rewarded for painting subsequently produced collages judged to be less creative.The most widely accepted explanation for these effects assumes that the presentation of reward orients the individual toward goal-relevant stimuli, thereby "diverting attention from the task itself and nonobvious aspects of the environment that might be used in achieving a creative solution" (Amabile, 1983, p. 120; see also Balsam & Bondy, 1983). According to this explanation, the narrowing of attention would reduce the spontaneity and flexibility of performance that results from high task involvement and contributes to creative performance.…”
mentioning
confidence: 99%